Dietary interventions in fibromyalgia: a systematic review. (29th March 2019) - Silva, Ana Rita; Bernardo, Alexandra; Costa, João; Cardoso, Alexandra; Santos, Paula; de Mesquita, Maria Fernanda; Vaz Patto, José; Moreira, Pedro; Silva, Maria Leonor; Padrão, Patrícia
Abstract: Fibromyalgia (FM) is a chronic non-degenerative disease, whose nutritional therapy seems controversial. This systematic review aimed to synthesize the knowledge about the effect of dietary interventions on patient-reported outcomes (PRO) and inflammation in patients with FM. Six electronic databases – PubMed, BioMed Central, Cochrane library, EMBASE, LILACS and ISI – were searched for clinical trials, in which a dietary intervention in patients with FM diagnosed was conducted. Quality of evidence assessment was measured in accordance with GRADE methodology. Seven clinical trials – 3 randomized controlled trials, 1 unrandomized clinical trial and 3 uncontrolled clinical trials were identified. Dietary approaches included gluten-free diet ( n = 1), raw vegetarian diet ( n = 2), low Fermentable oligo-, di- and monossacharides, alcohols and polyols (FODMAPs) diet ( n = 1), hypocaloric diet ( n = 2) and monosodium glutamate- and aspartame-free diet interventions ( n = 1). The major PRO were pain and functional repercussion, with 5 out of 7 studies reporting an improvement. The progress in secondary outcomes was reported for fatigue (2/5 studies), sleep quality (2/3 studies), depression and anxiety (3/6 studies), quality of life (4/5 studies), gastrointestinal symptoms (1/2 studies) and inflammatory biomarkers (1/1 study). However, according to Cochrane Risk of Bias, these studies had poor statistical quality. Well-designed studies should be performed to investigate the dietary interventions effect on FM. Key messages: Fibromyalgia (FM) is a chronic non-degenerative disease, whose nutritional therapy seems controversial but promising. Pain and functional repercussion in FM patients seem to improve with a hypocaloric diet, a raw vegetarian diet or a low FODMAPs diet, as much as quality of life, quality of sleep, anxiety and depression and inflammatory biomarkers. Existing studies in this subject are scarce and low quality, which does not allow conclusions to be drawn.